Төлепберген Қайыпбергеновтың дөретиўшилигинде инсан концепциясы типологиясы (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of creating a person’s image in the creative work of the people’s writer of Uzbekistan and Kara- kalpakstan, the great writer of the XX th century Karakalpak prose T.Kayipbergenov. There have been analysed such qualities as hu- manity, purity of soul, truthfulhess, honesty, good and evil, the broadness of the inner world of a person, as well as the narrowness of the